Effect of drying temperature and presalting methods on the quality and N‐nitrosamine formation of dried mud carp (Cirrhinus molitorella). Issue 8 (27th September 2018) - Zeng, Ping; Ruan, Qijun; Zhang, Yousheng; Ning, Zhengxiang; Zhang, Yehui; Cheng, Jingrong; Wang, Xuping
Abstract: The effects of drying temperature and pre‐salting methods on the quality and safety of dried mud carp were studied by evaluating appearance, texture properties, thiobarbituric acid, microstructure, microbial counts, total volatile basic nitrogen (TVBN), and the formation of N‐nitrosamine (NA) among the samples. Fish samples were dry‐salted with 0%–10% salt and dried at 15–45°C. The dried samples shown decreasing trend in the levels of rehydration property, b * (yellowness), TVBN, secondary lipid oxidation substrates (malondialdehyde), total microbial counts with increasing of salt contents. Using 15‐C drying, the dried mud carp with 4% (w/w) salt content shows an minimization of muscle decomposition and lower NAs content (5.38 μg/kg) compared with other samples, the myofibrillar bundle show more compact structure. Therefore, cold air‐drying is a promising method used to prepare hygienedried mud carp, it can also reduce the consumption of salt, which can be exploited by fish processors. Practical Applications: Mud carp ( Cirrhinus molitorella ) belongs to Class Osteichthyes, has a significant economic value in fishery. Currently, it is usually processed into dried products due to enormous production. However, the traditional process has two disadvantages: ne is drying process limited by climate, another is products' quality cannot be controlled. Herein, we reported the effects of drying temperature and pre‐salting methods on the quality and safety of dried mud carp, by evaluating appearance, texture properties, microstructure, microbia counts, total volatile basic nitrogen, and the formation of NAs among the samples.